Deferiprone versus deferoxamine in thalassemia intermedia: Results from a 5‐year long‐term Italian multicenter randomized clinical trial. Issue 7 (3rd May 2015) - Calvaruso, Giuseppina; Vitrano, Angela; Di Maggio, Rosario; Lai, Eliana; Colletta, Grazia; Quota, Alessandra; Gerardi, Calogera; Rigoli, Luciana Concetta; Sacco, Massimiliano; Pitrolo, Lorella; Maggio, Aurelio
<x xml:space="preserve">Abstract</x> In patients with thalassemia intermedia (TI), such as beta‐TI, alpha‐thalassemia (mainly HbH disease and mild/moderate forms of HbE/beta‐thalassemia), iron overload is an important challenge in terms of diagnosis, monitoring, and treatment. Moreover, to date, the only possible chelators available are deferoxamine, deferasirox, and deferiprone. Here, we report the first 5‐year long‐term randomized clinical trial comparing the effectiveness of deferiprone versus deferoxamine in patients with TI. Body iron burden, which was determined by measuring serum ferritin levels in the same patient over 5 years and analyzed according to the generalized linear mixed model (GLMM), showed a linear decrease over time in the mean serum ferritin levels in both treatment groups (P‐value = 0.035). The overall period of observation was 235.2 person‐years for the deferiprone patients compared with 214.3 person‐years for the deferoxamine patients. The results of the log‐rank test suggested that the deferiprone treatment did not affect survival compared with the deferoxamine treatment (P‐value = 0.360). The major adverse events observed included gastrointestinal symptoms and joint pain or arthralgia. Neutropenia and agranulocytosis were also detected, suggesting needing of strict hematological control. In conclusion, long‐term iron chelation therapy with deferiprone is associated with an efficacy and safety similar to that of deferoxamine, suggesting that this drug is an alternative option in cases in which deferoxamine and deferasirox are contraindicated. Am. J. Hematol. 90:634–638, 2015. © 2015 Wiley Periodicals, Inc.